A New Experimental Flap Design: The Saphenous Artery Periosto-Fasciocutaneous Flap of the Rat - BAYRAMİÇLİ, MEHMET NURİ ÜMİT (THIEME MEDICAL PUBL INC, 2012)
Vascularized periosteal graft is a frequently applied flap model for bone prefabrication studies due to its inhabitance of osteoprogenitor cells and osteoinductive potential. Various bones such as rib and fibula are reported as a potential source for the harvest of the periosteal flap in experimental studies on higher species such as dogs and pigs, which necessitates a rather complicated and expensive experimental setting. Therefore a reliable and inexpensive small animal model on vascularized periosteal flaps is necessary for future research. A new saphenous artery based periosto-fasciocutaneous flap model in rats is described here, which is easily dissected and monitorized. In this experimental study, 15 male Sprague Dawley rats were operated and killed following a 3-month-long follow-up period. The histological analysis revealed heterotopic osteoneogenesis in 12 of 15 flaps (80%), whereas 14 flaps (93.3%) exhibited signs of angioneogenesis originating from the periostofasciocutaneous flap. The presented flap model promises to be an appropriate alternative for new studies where bone prefabrication methods are evaluated.
Keywords: osteoneogenesis; periosteum; saphenous artery; VASCULARIZED PERIOSTEUM; OSTEOGENIC CAPACITY; BONE; GRAFTS